A comparison between video-assisted teaching (VAT) and traditional teaching (TT) methods on knowledge and confidence level on performing focus assessment with sonography for trauma (FAST) among final year medical students in emergency department teaching hospital northeastern Malaysia - Mohamed Ahmed, Mohamed Abdallah; Fauzi, Mohd Hashairi; Yazid, Mohd Boniami; Ahmad, Mohammad Zikri; Wan Mohamad, Wan Syahmi; Baharuddin, Kamarul Aryffin; Abdull Wahab, Shaik Farid (Faculty of Medicine, 2025)
In response to the COVID-19 pandemic in 2020, many universities switched from face-to-face teaching to alternative forms of delivery without jeopardizing the quality of teaching and learning due to lockdown. Our study aims to discover the alternative way of teaching ultrasound among medical students and uses Focused Assessment with Sonography in Trauma (FAST) as an example of training. A prospective interventional study was conducted involving 100 final-year medical students. The study’s primary endpoint was to compare the level of knowledge and confidence pre- and post-workshop of FAST scan among medical students who received Video-Assessed Teaching (VAT) versus those who received Traditional Teaching (TT). Our study showed a significant improvement in knowledge and confidence after the workshop. There was a significant mean difference between pre- and post-workshop for both knowledge and confidence among both groups (VAT and TT) (P <0.001). However, the two groups had no significant mean difference in knowledge and confidence levels (P >0.050). It was noticed from students’ responses that 31% preferred the hands-on session, 28% preferred bedside teaching, while few preferred lectures and videos, with 20% and 18%, respectively. VAT is non-inferior compared to TT in terms of knowledge and confidence in training ultrasound among undergraduate students. Thus, VAT can be considered an alternative method of teaching during a pandemic outbreak, with certain limitations.